3D virtual reconstruction of the Pokrovska Church in Sumy city - Tytarenko, Ihor; Leonets, Yurii; Pavlenko, Ivan; Andrusiak, Vladyslav; Kulikov, Oleksandr (DataverseUA, 2025)
The researched materials concern the virtual reconstruction of the Pokrovska Church in Sumy, an 18th-century architectural monument destroyed by the Soviet Union in 1932. The church was built between 1783 and 1790 in the late Baroque style on the site of previous wooden churches and was intended as the regimental church of the Sumy Sloboda Cossack Regiment. During the Soviet period, the church was closed, used for economic purposes, and destroyed in 1932. The digitization aims to document its historical role, architectural value, and the loss of a cultural heritage site for future remembrance and restoration. The developed 3D model covers the terrain of the historical center of Sumy city, specifically within Pokrovska Square, considering available historical data and archival descriptions of historical monuments.